Enhance sustainable methane production from anaerobic co-digestion of POME using UASB (hydraulic retention time) - Tan, Jia Xiang (2018)
Palm Oil Mill Effluent (POME) is a waste of palm oil mills. This material is highly biodegradable and produces tremendous amount of methane gases when it is being digested. Most palm oil mill treats this material by leaving it in an open environment pond. The POME left in the pond will decompose and release methane gas into the environment. Methane gas is 20 times stronger than carbon dioxide to cause greenhouse effect as it destroys the atmosphere rapidly. In order to prevent the release of methane gas into the environment, the decomposition of POME must occur in a closed environment. Anaerobic digestion is a method that allows material to decompose without the presence of oxygen. Anaerobic co-digestion can improve the methane yield when different type of material are mix together. In this study, cow manure is mixed with POME for the co-digestion process at a ratio of 50:50. Upflow Anaerobic Sludge Blanket (UASB) reactor allows waste mixture to decompose within an enclosed environment. The sludge blanket consist of microorganism that digest the waste as it passes through it. During digestion the waste will produce methane gases which will then be collected by the equipment for other purposes. In this paper, we will be studying the effects of Hydraulic Retention Time (HRT) on the yield of methane gas. Hydraulic retention time are known as the average length of time that a compound remains within a storage unit before it is being discharge. HRT is important since the growth of anaerobic bacterial depends on the quantity of time needed and subsequently converting organic material to biogas. Hydraulic retention time is dependable on the flow rate of the effluent into the reactor. For this study, three retention time of 5, 10 and 15 days are conducted based on flow rate of 200, 100, 66.67 mL/day. The flow rate is based on how many days is required for 1000 mL of effluent to pass through the reactor. At the end of the study, the results showed that HRT 15 days showed the highest amount of methane yield with a flow rate of 66.67 mL/day. This shows that the waste material needed more time in order for it to digest entirely to produce high amount of methane gas.